Association of UHR and ECG parameters with type 2 diabetes mellitus in non-alcoholic fatty liver disease - Wang, Yaping; Liu, Mingyan; Li, Wei; Liu, Yaping; Tang, Xiaowei; Sun, Fei; Zhu, He; Tang, Xiangming (Frontiers in Endocrinology, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) is the most prevalent liver disease globally. NAFLD increases the risk of type 2 diabetes mellitus (T2DM) while lacking clinical predictors. This study aims to investigate the characteristics and clinical significance of the uric acid (UA) to high-density lipoprotein cholesterol ratio (UHR) and electrocardiogram (ECG) parameters in NAFLD patients, both with and without T2DM.MethodsWe compared 102 NAFLD with T2DM (NAFLD-T2DM) cases to 113 NAFLD without T2DM (NAFLD-nT2DM) cases. Baseline data and biochemical indicators, including UHR, were collected and analyzed in each group. A 12-lead ECG was used to collect parameters that were compared between the two groups. Multivariate logistic regression analysis was employed to identify factors influencing NAFLD with T2DM. Receiver operating characteristic (ROC) curves were utilized to assess the clinical value of UHR combined with ECG parameters in identifying T2DM risk among NAFLD patients.ResultsCompared to the NAFLD-nT2DM group, the NAFLD-T2DM group exhibited significantly higher levels of triglycerides (TG), fasting plasma glucose (FPG), UA, and UHR, while aspartate aminotransferase (AST) levels were lower (P < 0.05). The incidence of ST-T changes, heart rate, and P wave duration was also higher in the NAFLD-T2DM group, whereas the QT interval was shorter (P < 0.05). Multivariate logistic regression analysis revealed that UHR, ST-T changes, heart rate, QT interval, and P wave duration are independent factors associated with the incidence of T2DM in NAFLD. ROC curve analysis indicated that the area under the curve (AUC) for the combination of five variables in predicting T2DM in NAFLD was 0.949 (95% CI: 0.905-0.977, P < 0.05), with a sensitivity of 91.96% and a specificity of 93.55%, significantly superior to those of individual indicators.ConclusionUHR and ECG parameters are associated with T2DM in NAFLD patients. The combination of UHR and ECG parameters demonstrates predictive value for the incidence of T2DM in NAFLD patients. Clinical attention should be directed toward the levels of UHR and ECG parameters in NAFLD with T2DM.